Legal Protection for Women and Children with Disabilities in Indonesia - Dewa Gede Sudika Mangku (University of Udayana, 2021)
The state has an obligation to protect its citizens, including the protection of women and children with disabilities. Given that people with disabilities remain the most vulnerable and marginalized group in every society, even though the international and national human rights movements have improved, in general this group is still in the last row enjoying it. The purpose of this research is to analyze and study legal protection for women and children with disabilities and the obstacles that exist in Indonesia. The research method used in this research is normative juridical, with the approach used the statutory approach. The results of his research show that women and children with disabilities in Indonesia have obtained legal protection based on human rights law and international treaties that have been ratified by the Indonesian government, although in implementation there are still obstacles that occur but this does not prevent fulfillment of the rights of persons with disabilities in Indonesia, especially for women and children.